Respuesta fisiológica del cultivo de maíz (zea mays) bajo estrategias de riego deficitarío - Moreira Solórzano, Hedy Jairo (2022)
The present investigation was carried out at Escuela Superior Politécnica Agropecuaria de Manabí, Manuel Félix López with the objective of evaluating the physiological response to several strategies of deficit irrigation in the cultivation of corn (Zea mays). The experiment was carried out under a Randomized Complete Block Design (DBCA) carrying out 6 treatments with 4 replicates giving a total of 24 experimental units; 3 methods of deficit irrigation were evaluated; the ORDI methodology (optimized regulated deficit irrigation), the PRD (partial root drying) and the combination of ORDI plus PRD. The variables evaluated were plant height, biomass, stomatal conductance, water productivity, and soil matric potential. In the area biomass variable, no significant differences were found (p>0.05) the treatment with the highest average in leaf biomass was T2 with 40.25 g and stem biomass 74.33 g, in the variable biomass if significant root differences were found, the treatment with the highest average was T6 with 44.55 g. The humidity data had different data between treatments, T1 and T2 being the depth with the greatest humidity 5 cm and 15 cm on the left side, treatment T3 and T4 having the greatest humidity at the depth of 35 cm and 45 cm. The effect of deficit irrigation was the decrease in aerial biomass of the treatments with deficit, the most significant differences were seen in the treatments that had PRD 2 weeks with a greater decrease in biomass.